Non-Hamiltonian Actions and Lie-Algebra Cohomology of Vector Fields - Ferreiro Pérez, R.; Muñoz Masqué, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
Two examples of Diff⁺S¹-invariant closed two-forms obtained from forms on jet bundles, which does not admit equivariant moment maps are presented. The corresponding cohomological obstruction is computed and shown to coincide with a nontrivial Lie algebra cohomology class on H²(X(S¹)).